Thoughts Out of Season, Part II - Nietzsche, Friedrich Wilhelm, 1844-1900; Collins, Adrian (Salt Lake City, UT : Project Gutenberg, 2011)
"Thoughts Out of Season, Part II" by Friedrich Wilhelm Nietzsche is an essay written in 1874. This work examines the proper role of historical knowledge in human life, challenging the prevailing notion of "knowledge as an end in itself." Nietzsche proposes an alternative approach where living becomes the primary concern, arguing that this perspective could improve society's health. The essay attacks both historicism and the possibility of objective understanding, while introducing Nietzsche's increasingly elitist philosophy about humanity's true purpose and meaning. (This is an automatically generated summary.)
The use and abuse of history -- Schopenhauer as educator.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Untimely_Meditations
Release date is 2011-12-05
Produced by Marc D'Hooghe, Charles Franks, Michael Roe and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: History -- Study and teaching; Schopenhauer, Arthur, 1788-1860